2002
DOI: 10.4028/www.scientific.net/msf.408-412.511
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Characterization of Twins Using Automated Electron Backscatter Diffraction

Abstract: Abstract. This paper describes results obtained using an automated, crystallographically-based technique for twin identification. The technique is based on the automated collection of spatially specific orientation measurements by electron backscatter diffraction (EBSD) in the scanning electron microscope (SEM). The key features of the analysis are identification of potential twin boundaries by their misorientation character, identification of the distinct boundary planes among the symmetrically equivalent can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Mason et al [19] and Wright et al [20] developed a protocol for the identification of twin boundaries, the discrimination of twinned from untwinned material and the estimation of area fraction of each twin type from EBSD data. Twin boundaries have specific crystallographic properties that enable their analysis from 2-dimensional sections beyond that for general high-angle boundaries (GHABs).…”
Section: Analysis Of Twins From Ebsd Datamentioning
confidence: 99%
“…Mason et al [19] and Wright et al [20] developed a protocol for the identification of twin boundaries, the discrimination of twinned from untwinned material and the estimation of area fraction of each twin type from EBSD data. Twin boundaries have specific crystallographic properties that enable their analysis from 2-dimensional sections beyond that for general high-angle boundaries (GHABs).…”
Section: Analysis Of Twins From Ebsd Datamentioning
confidence: 99%
“…The most correct twin data would be achieved by using all three twin criteria in sequence. However, Wright et al [26] have reported that difficulties exist with the grain boundary trace criterion, so in this study, only the misorientation and K 1 plane coincidence criteria were tested in combination with manual parent selection. Table III shows the results of these tests compared with the baseline analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The line of intersection of the predicted twin plane and the sample section plane should be parallel to the experimental grain boundary. The details of this comparison are discussed by Wright et al [26] This third criterion is called the twin boundary trace comparison. Mason et al [23] provided explicit examples of these three criteria with corresponding advantages and limitations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations